Pengembangan Media Pembelajaran Pop-up Book Berbasis Kontekstual Muatan Pelajaran PPKN Kelas IV Sekolah Dasar - Salsabila, Izzah; Ninawati, Mimin (Jurnal Paedagogy, 2022)
This study aims to develop a product which is a Pop-up Book media in the content of civic education about religious diversity material in Indonesia for 4th-grade students. This study used the R&D method (Research and Development) with a 4D model. The stages in the 4D model consist of Define, Design, Develop, and Disseminate. This research was conducted at SDN Slipi 01 Pagi involving 29 students from class IV B. The data were collected using questionnaires distributed to media experts, material experts, and students. The data analysis technique used descriptive statistical analysis as percentage analysis. The results of the research showed that the Pop-up Book media development had an average percentage of 92% in the "very good" category based on media experts, 100% in the "very good" category based on material experts, and an average percentage of 99% in the "very good" category based on student responses. It can be concluded that the Pop-up Book media in the civic education about religious diversity in Indonesia is categorized as very good and can be one of the media solutions that aim to support the learning process.